COMPLEX TREATMENT OF YOUTH EPIPHYSEOLYSIS OF THE FEMORAL HEAD IN CHILDREN - Urinbayev Payzilla Urinbayevich; Eranov Nurali Fayziyevich; Norbadalov Faxriddin Xolmirzayevich; Khudoyberganov Sodik Toshtemirovich; Amonov Gayrat Tursunovich; Eranov Sherzod Nuraliyevich (Scholar Express Journals, 2022)
The article provides an analysis of the results of treatment of 20 patients with SCFE. In the course of the disease, an acute course was observed in 10 patients and a chronic course in 10 patients. The duration of the disease is from 2 to 5 years. Patients were treated separately in groups: the 1st group was conservative, the 2nd group was traditional operative, and the 3rd group was modern percutaneous osteosynthesis. The results of the study show that the reduction of JEFH in skeletal traction and percutaneous osteosynthesis provide the best positive results in 88.8% of patients. According to the treatment of JEFH, it is indicated that in the treatment of juvenile epiphysiolysis there should be a skillful combination of both conservative and surgical methods of treatment
Keywords: Juvenile Epiphysis Of The Femoral Head; Skeletal Traction; Percutaneous Osteosynthesis